2017
DOI: 10.1080/10095020.2017.1333715
|View full text |Cite
|
Sign up to set email alerts
|

Coastal zone management in India − present status and future needs

Abstract: The coastal zone is a region where land, ocean and atmosphere interact and hence it is dynamic in nature. India has a long coastline which was not adequately monitored until the advent of the satellite remote sensing era in the 70s. India has a very robust remote sensing program that the Indian Remote Sensing Satellite (IRS) series of satellites were effectively used to monitor coastal habitats, landforms, shoreline, water quality, etc., and changes were identified during the last 40 years. The classification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 40 publications
(38 reference statements)
0
17
0
Order By: Relevance
“…Vulnerability Index of Tamil Nadu coastal zone. Geospatial information technology can contribute greatly to develop such models (Nayak, 2017). The current study has identified the most vulnerable coastal villages through the vulnerability mapping of LECZ regions based on average population density and hence can aid in the development of disaster management plans for the east coast of India.…”
Section: Discussionmentioning
confidence: 99%
“…Vulnerability Index of Tamil Nadu coastal zone. Geospatial information technology can contribute greatly to develop such models (Nayak, 2017). The current study has identified the most vulnerable coastal villages through the vulnerability mapping of LECZ regions based on average population density and hence can aid in the development of disaster management plans for the east coast of India.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between the land, ocean, and atmosphere in the coastal zone makes it highly dynamic in terms of structure and functioning [1]. Due to the high productivity of coastal areas, they are also among the most exploited and threatened geomorphic units and ecosystems on the earth [2].…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable management of the coastal zone requires accurate information on the various aspects that affect it, e.g., information on the local coastal habitats, coastal processes, natural hazards and their impacts, water quality, and living resources [1]. Effective management practices also depend on indigenous/local knowledge and suitable responses from concerned government agencies.…”
Section: Introductionmentioning
confidence: 99%
“…They are important ecological systems and vital assets for many nations, which are also complex and dynamic environments where a vast array of coupled biological, chemical, geological, and physical processes occur over multiple temporal and spatial scales [2]. Coastal areas (within 100 km from the coast) are regions where land, ocean and atmosphere interact, with approximately 60% of the world's population, and have a direct interface with food supply and human health [3,4]. Coastal waters are under pressure from direct human activities and climate changes due to their close proximity to human population [5,6].…”
Section: Introductionmentioning
confidence: 99%